Residual ciprofloxacin in chicken manure inhibits methane production in an anaerobic digestion system - Yiting Wang; Qing Liu; Hongli Ran; Pingcai Peng; Yan Wang; Guoliang Peng; Yinbao Wu; Xin Wen (Poultry Science)
Anaerobic digestion (AD) is commonly used to dispose of laying hen manure. However, veterinary antibiotic residues present in chicken manure may affect the AD process. Here, the effects of three types of veterinary antibiotics commonly used in laying hen breeding on AD were explored. Manures containing antibiotics at two different concentrations were continuously added during AD for 5 days: amoxicillin (HAMX: 145.06 mg/kg, LAMX: 57.88 mg/kg), doxycycline (HDOC: 183.61 mg/kg, LDOC: 98.00 mg/kg), and ciprofloxacin (HCIP: 96.34 mg/kg, LCIP: 40.43 mg/kg). Compared with a control with no veterinary antibiotics, the amoxicillin and doxycycline groups presented no significant effects on biogas production, methane production, VFA concentration, acetic acid concentration or the pH of the AD system (P > 0.05). However, compared with the control, the ciprofloxacin groups presented significantly inhibited biogas and methane production during AD (P < 0.05), and the HCIP and LCIP groups presented significantly decreased biogas (47.82% and 45.37%, respectively) and methane (58.24% and 52.55%, respectively) production (P < 0.05). Moreover, the VFA and acetic acid concentrations of the ciprofloxacin groups were significantly higher than those of control during the entire AD period (P < 0.05), and the pH value at the withdrawal stage was significantly lower than that of the control group (P < 0.01), with no significant difference between the HCIP and LCIP groups (P > 0.05). Our results suggest that ciprofloxacin causes VFA and acetic acid accumulation in AD systems, thereby reducing the pH of the systems and inhibiting methanogen growth, ultimately reducing methane production in the AD systems. These findings contribute to a deeper understanding of the impact of ciprofloxacin on methane production in AD systems and offer some considerations for the application of AD systems.